Students' Creative Thinking Skill in Solving Higher Order Thinking Skills (HOTS) Problems - Zaiyar, M; Rusmar, Irfan (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
Creative thinking skills one of the important aspects that must be possessed by students' mathematical thinking skills to connect mathematical concepts as well as the development of thinking processes in solving mathematical problems. The purposes of this research are to determine the level of students' creative thinking skills in solving Higher-Order Thinking questions and to investigate the students' creative thinking skills in solving Higher Order Thinking Questions. This research employed the descriptive qualitative method with 28 students who have passed the Calculus subjects the samples of the research determined through nonprobability sampling. The data were collected through tests and interviews. The research discovered that the average score obtained was 38.43%, specifically35.71%of the students were at the very creative level, 50% of the students were at the creative level, and 14, 29% of the students were at the fairly creative level. Students' creative thinking skills were lacking in creativeness and detail indicators. They were not able to solve problems properly and correctly. The fluency and flexibility indicators were in a good category. So, it can be concluded that the level of students’ creative-thinking skills in solving the Higher-Order Thinking Skills problems was at the creative level.